The role of transformational leadership and work motivation on employee performance - Rohman, Abdul; Oktapiani, Putri Eriana; Pujaroh, Siti; Haryadi, Didit (Trigin Publisher, 2024)
Employee performance is an essential factor influencing success. In an organization, this is one of the most critical functions of a company. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study used an associative descriptive quantitative method with a population of 43 respondents drawn into a sample using non-probability sampling, saturated sampling / total sampling method—and data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis of transformational leadership does not affect employee performance. Thus, the second hypothesis states that employee performance is influenced by work motivation, meaning that the higher the work motivation, the higher the employee performance will be. The third hypothesis is that employee performance is influenced by transformational leadership and work motivation that can simultaneously improve employee performance. This research is expected to provide theoretical contributions to the literature in this context, certainly in the context of human resource management.